PENERAPAN ALGORITMA BLOWFISH DAN ELGAMAL UNTUK PENGAMANAN DATA SEKUNDER DATABASE - Harry Darmawan Siregar (2021)
Technological developments have resulted in the use of information technology, one of which is the usage of e-commerce. E-commerce had been applied to various platforms such as personal computers (PCs) and mobile smartphones. Because there are many different platforms, there are also many users. The users of E-commerce are required to insert their personal data such as phone number, name, and address where those data are called secondary data in a database which is not secured almost on all databases. This kind of data are can be very important too because the irresponsible people who steal and got this data can abuse it to do bad things like selling it. Based on this case, this research wants to research how to improve the security of secondary data information by applying the combination of Blowfish and Elgamal algorithms to the secondary data database so that it can be more secured in case if there is data leakage. Data security by encrypting with Blowfish then ciphertext will be re-encrypted again with Elgamal is expected to improve data security in the database so that E-commerce users can feel more secure when entrusting their data during registration. The output obtained from this research are the application of the Blowfish algorithm and the Elgamal algorithm which can improve data security from possibility of brute force attacks on secondary data ciphertext in the database by applying it to website-based software with encryption and decryption process time and efficient use of resources.